Changing ideological and implementational spaces for minoritised languages in higher education: Zapotequización of language education in Mexico. Issue 6 (3rd July 2019) - De Korne, Haley; López Gopar, Mario E.; Rios Rios, Kiara
ABSTRACT: Indigenous languages of Mexico have largely been excluded from formal education spaces. This ethnographic action research study highlights a context where Diidxazá / Isthmus Zapotec, an Indigenous language of Oaxaca, has recently begun to be taught in higher education. We examine the ways that administrators, the teacher, and students in these classes have collaborated to create a new space within the institution. By tracing the power dynamics behind the implementational and ideological efforts that have made this possible, we aim to provide insight into the social change underway in this setting, as well as the concrete steps that were taken in the creation of this pluralist space for Indigenous language learning. We conclude with a discussion of the collective engagement that has been necessary in order to foster and develop a community of Indigenous-language learners, and the challenge of going beyond tokenistic inclusion of minoritised languages in education.